Analysis of Executive Succession Planning in 12 Construction Companies. Issue 1 (2nd January 2017) - Perrenoud, Anthony J.; Sullivan, Kenneth T.
ABSTRACT: The most vital resource in a construction company is the executive leadership. Therefore, executive succession can significantly affect a company, with the potential to cause both visible and invisible negative impacts. Changes in leadership can cause turmoil, both financially and operationally; unless minimized through careful succession planning. Research on succession planning shows that beginning to prepare for leadership transition before it occurs can minimize potential negative impacts. Despite the importance of succession planning, little research is available on how to improve leadership transitions in the construction industry. Thisarticler presents the findings from interviewing 12 former and current executives at construction companies that experienced leadership transitions. The findings include insight regarding the methods the companies used to plan and implement executive succession. This article also discusses the correlation between the number of succession practices a company applies and the executive's level of satisfaction with the leadership transition. The results of Spearman's rank-order correlation and linear regression analysis indicate a strong positive correlation exists between the number of practices implemented and the satisfaction level.